2016
DOI: 10.3402/gha.v9.32505
|View full text |Cite
|
Sign up to set email alerts
|

Assessing evidence of inequalities in access to medication for diabetic populations in low- and middle-income countries: a systematic review

Abstract: BackgroundInequalities in access to medications among people diagnosed with diabetes inlow- and middle-income countries (LMICs) is a public health concern since untreated diabetes can lead to severe complications and premature death.ObjectiveTo assess evidence of inequalities in access to medication for diabetes in adult populations of people with diagnosed diabetes in LMICs.DesignWe conducted a systematic review of the literature using the PRISMA-Equity guidelines. A search of five databases – PubMed, Cochran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…The socioeconomic inequalities we observed in the utilisation of hypertension and T2D management services in Indonesia are consistent with findings on socioeconomic inequalities in access to NCD‐related healthcare services in HICs and some LMICs . Our results can be interpreted in relation to three important, interrelated dimensions in access to health care: the approachability, availability and affordability of services .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The socioeconomic inequalities we observed in the utilisation of hypertension and T2D management services in Indonesia are consistent with findings on socioeconomic inequalities in access to NCD‐related healthcare services in HICs and some LMICs . Our results can be interpreted in relation to three important, interrelated dimensions in access to health care: the approachability, availability and affordability of services .…”
Section: Discussionsupporting
confidence: 89%
“…Many LMICs struggle to provide adequate access to NCD management for all population groups, in particular for lower‐income groups . Multi‐country studies have shown that socioeconomic inequalities in the management and prevalence of NCDs exist in high‐income countries (HICs) and in some LMICs . The prevalence of NCDs is higher in lower‐socioeconomic groups, creating a sense of urgency for countries to design and implement strategies to safeguard access to NCD management services for those who need it most.…”
Section: Introductionmentioning
confidence: 99%
“…This limitation, if not corrected, will continue to hamper the effective management of the disease. The finding supports research highlighting that patients living in rural areas were at a greater disadvantage in accessing health care services and managing chronic diseases [15,26].…”
Section: Discussionsupporting
confidence: 81%
“…Barriers to accessing diabetes health care in developing countries include affordability, poor access to healthcare facilities and essential medicines, and a lack of sustainable financing and reliable supply systems (Table ). Patients with diabetes living in rural or remote areas, those with a low education level, and those with a low income or low SES have low access to diabetes medications, primarily due to inconsistent policies towards primary health care . The increasing cost of insulin and medications, primarily borne by underserved populations, is an additional area of concern …”
Section: Managementmentioning
confidence: 99%